PENINGKATAN KETERAMPILANMENULIS KARANGAN DESKRIPSI MENGGUNAKAN PENDEKATAN KONTEKSTUAL BERBANTUAN MEDIA GAMBAR BERSERI SEKOLAH DASAR - Rizky, Erawati; Halidjah, Siti; Margiati, K Y (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe general problem in this study is whether using a serialized assisted contextual approach can improve the writing skills of the third grade students of Southeast Pontianak 09? The general purpose of this study is to describe the use of a serial image-assisted contextual approach in order to improve the writing skills of the third grade students of South Pontianak 09 in South Pontianak. This study uses descriptive methods with the form of classroom action research, and the nature of research is collaborative. The research setting took place at the 09 Pontianak Public Elementary School with research subjects namely class III students totaling 22 people. Data collection techniques used are interview techniques, direct observation techniques, measurement techniques with data collection tools namely observation sheets. The data collected is analyzed by an average calculation. This research was conducted in 3 cycles. In cycle 1 the average value of students was 71.59. Whereas in cycle 2 the average value of students to be 75.38 increased by 3.79. In cycle 3 the average value of 78.79 students increased by 3.41. With the use of a contextual approach assisted with serial images media on Indonesian language learning, it can improve the description writing skills, so that it can be concluded that the use of serialized contextual media assisted approaches can be used to improve the writing skills of the third grade students in Southeast Pontianak 09 State Elementary School.Â Keywords: Improvement, Writing Skills, Descriptive Descriptions, Sexual Approach, and Serial Image Media.